Transmigration, ethnic sentiment, and inter-ethnic conflict in Aceh - Cut Maya Aprita Sari,; Kartini Aboo Talib @ Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The discovery of natural gas and oil resources in the 1970s caused the Indonesian government to establish various industries in Aceh. In order to implement this new project, the government started a transmigration program by sending ethnic Javanese to work in factories in Aceh. Since then, the Javanese in Aceh have been given privileges by the Indonesian government (which is also dominated by the Javanese). This situation creates ethnic sentiments because the Acehnese lost their homes and did not have jobs. This study aims to find out the forms of ethnic sentiments that arise due to the transmigration of Javanese to Aceh, thus giving implications to the inter-ethnic conflict that has existed for a long time in Aceh. Using a qualitative methodology based on descriptive analysis of case studies, this study found two forms of ethnic sentiment. First, ethnic prejudice and discrimination, which have formed a relationship of reciprocal reactions. Discrimination, rooted in the Indonesian government's discrimination towards the Acehnese, led to the establishment of The Free Aceh Movement (GAM). The aim was to counter Javanese domination, resulting in prolonged interethnic conflict. Second, Differences in ethnic identity, such as Aceh prioritizing Islamism and Javanese prioritizing Javanism, further exacerbated ethnic disparities in ethnocentrism. These two forms of ethnic sentiment have significantly contributed to interethnic conflict in Aceh.